MODELO DE GESTÃO PARA INCUBADORA DE EMPRESAS SOB A PERSPECTIVA DE METODOLOGIAS DE GESTÃO APOIADAS EM REDE: O CASO DA INCUBADORA DE EMPRESAS DE BASE TECNOLÓGICA DA UNIVERSIDADE FEDERAL FLUMINENSE - Ribeiro, Ana Cristina Silva (2008)
This work presents the construction and improvement of the management model of Technological Base Enterprises Incubator of UFF, under the perspective of management methods supported on Triple Helix network, and also using some Balanced Scorecard elements. It ends to show the Incubator career, goal and specific setting, starting from the articulation of inside (academic community) and outside partnerships with several innovation system actors, such as Technology Networks, the other Incubators from Rio de Janeiro and the National Association of Technologic Enterprises Promoting Corporations (Associação Nacional de Entidades Promotoras de Empreendimentos de Tecnologias ANPROTEC). Models of Knowledge Management, Triple Helix and Balanced Scorecard will be used as theoretical support for analyses, also showing up socio-technical network part